POTENSI KANDUNGAN ANTIOKSIDAN RUMPUT KEBAR (Biophytum Petersianum Klotzsch) TERHADAP APOPTOSIS DAN GAMBARAN HISTOPATOLOGIS TESTIS PADA MENCIT (MUS MUSCULUS) YANG DIPAPAR 2,3,7,8-Tetrachlorodibenzo-p-dioxin - Dewita, Dewita; Widjiati, Widjiati; Rimayanti, Rimayanti; Suprayogi, Tri Wahyu; Hariadi, Mas'ud; Plumeriastuti, Hani (Universitas Airlangga, 2019)
2,3,7,8-Tetrachlorodibenzo-p-dioxin (TCDD) is the most toxic compound in the dioxin group. This compound is a pollutant for the environment and very harmful to human health and enter the body through the mucous membranes in the mouth and the respiratory tract and can be transmitted through the placenta and lactation. The aim of this study was to know the antioxidantpotency of to resolve reproduction disturbance caused by TCDD exposure.Thirty Balb/C male mice were divided into five different groups, the negative control group, a positive control group exposed to TCDD at a dose of 7 Î¼g/kg BW, P1 group of groups exposed to TCDD doses of 7 Î¼g / kg BW and given Biophytum petersianum extract 0.05mg/gBB/day, group P2 group exposed to TCDD doses of 7Î¼g/kgBW and given 0.080mg/gBB/day, and group P3 were exposed to TCDD dose of 7Î¼g/kgBB and given the extract of Biophytum petersianum 0.135mg/gBB/day during day 2 to day 55. On the 56th day the mice were sacrificed and apoptotic examination and spermatogenic cell histopathological features were performed on the testis. The results showed that: P2 (0,433 ± 0,497; p<0,05) and P3 (0,200 ± 0,000 p<0,05) groups were the most effective group in decreasing spermatogenic cell apoptosis compared to positive control group (2,933 ± 1,5832 p<0,05). The Johnsen score result showed that P2 (9,400 ± 0,420) and P3 (9,800 ± 0,253) groups improving the histopathologic picture of spermatogenic cells in seminiferous tubules compared to positive control group (7,20 ± 0,400) p<0,05. Conclusion of this study were Biophytum petersianum is effective to solve reproduction disturbances caused by exposure of TCDD and the P3 group is the most effective group.